Habakkuk - Thomas, Heath 1975- (Chicago Wm. B. Eerdmans Publishing Co., 2018)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Part I: Introduction and Commentary -- Introduction -- Hearing Habakkuk -- Biblical and Systematic Theology -- The Poetry of Habakkuk -- The Theology of Habakkuk -- Habakkuk in the Church -- Conclusion -- Habakkuk 1 -- Translation -- Summary -- Commentary -- Excursus: The Power of Lament Prayer -- Habakkuk 2 -- Translation -- Summary -- Commentary -- Excursus: The Power of Silence -- Habakkuk 3 -- Translation -- Summary -- Commentary -- Excursus: The Power of Memory -- Part II: Theological Horizons -- Major Themes in the Minor Prophet: Habakkuk and Biblical Theology -- Introduction -- Habakkuk in the Old Testament -- The New Testament -- Conclusion -- Centering Shalom: Habakkuk and Prayer -- Introduction -- Relating Shalom and Prayer -- God's Shalom World and Prayer -- Shalom Shattered -- Shalom in the New Creation -- Dead Ends to Doorways: Habakkuk and Spiritual Formation -- Introduction -- Dead Ends -- Doorways -- Select Bibliography -- Author Index -- Subject Index -- Scripture Index.
Description based on publisher supplied metadata and other sources
Keywords: Bible. Habakkuk--Commentaries; Electronic books; Kommentar